Recent Evidence on Perception and Esthetic Appreciation: The Role of Value and Expertise in Canon Formation. (April 2014) - Consoli, Gianluca
On the basis of current evidence derived from neurocognitive research, it is possible to mediate two alternative theories concerning the relationship between perception and esthetic appreciation, in particular by distinguishing between high-quality images and popular.